Conditioning China's Influence: Intentionality, Intermediaries, and Institutions. Issue 139 (2nd January 2023) - Fung, Courtney J.; Han, Enze; Quek, Kai; Strange, Austin
ABSTRACT: According to popular accounts, China's international influence is increasing with its growing material capabilities. However, researchers repeatedly demonstrate gaps between China's power and its influence. Building on earlier research, we propose an inclusive approach to conceptualizing China's influence abroad. Our approach conditions China's net influence on three dimensions. First, intentionality distinguishes between intentional influence-seeking and influence that accrues unintentionally via influence externalities. Second, a systematic treatment of Chinese intermediaries –the diverse set of substate actors operating overseas–is needed in order to expand the study of Chinese influence beyond state-level behavior. Finally, domestic institutions in host countries are essential conduits for conditioning how the behavior of Chinese actors, as well as group and individual reactions within host countries, are aggregated up to the policy level.